Multiple myeloma presenting as pancoast tumour- A case report - Bhuvana Jayaprakash; Manjunath Nandennavar; Shashidhar V Karpurmath (South Asian Journal of Health Sciences, 2026)
Extramedullary manifestations of plasma cell neoplasms are uncommon and may pose significant diagnostic challenges because of their ability to mimic primary thoracic malignancies. Thoracic plasmacytomas represent a rare subset of extramedullary disease and frequently resemble primary lung cancer, metastatic disease, lymphoma, or sarcoma on imaging. We report a middle-aged man who presented with progressive left upper chest pain radiating to both upper limbs, associated with a large chest wall swelling, exertional dyspnea, and dry cough. Imaging revealed a giant transthoracic mass involving the thoracic inlet with encasement of the brachial plexus and subclavian artery, extensive rib destruction, and widespread osteolytic skeletal lesions. The lesion was initially considered a Pancoast tumour. Histopathological examination demonstrated a plasma cell neoplasm, while immunohistochemistry showed strong CD138 and MUM1 expression with lambda light-chain restriction. Bone marrow biopsy confirmed marrow plasmacytosis. The final diagnosis was multiple myeloma presenting with a giant paraskeletal thoracic plasmacytoma. Treatment with bortezomib, thalidomide, and dexamethasone (VTD regimen) along with palliative radiotherapy was planned; however, therapy could not be initiated because of financial constraints. Giant paraskeletal thoracic plasmacytoma presenting as a pancoast tumour mimic is exceedingly rare. Plasma cell neoplasms should be considered in the differential diagnosis of destructive apical thoracic masses associated with osteolytic skeletal lesions. Histopathological confirmation remains essential for establishing the diagnosis and guiding management.